Perineuronal net density in schizophrenia: A systematic review of postmortem brain studies - Lisboa, João Roberto F.; Costa, Olga; Pakes, Gustavo Henrique; Colodete, Debora Akemi E.; Gomes, Felipe V. (Schizophrenia research, 2024)
The onset of schizophrenia is concurrent with multiple key processes of brain development, such as the maturation of inhibitory networks. Some of these processes are proposed to depend on the development of perineuronal nets (PNNs), a specialized extracellular matrix structure that surrounds preferentially parvalbumin-containing GABAergic interneurons (PVIs). PNNs are fundamental to the postnatal experience-dependent maturation of inhibitory brain circuits. PNN abnormalities have been proposed as a core pathophysiological finding in SCZ, being linked to widespread consequences on circuit disruptions underlying SCZ symptoms. Here, we systematically evaluate PNN density in postmortem brain studies of subjects with SCZ. A systematic search in 3 online databases (PubMed, Embase, and Scopus) and qualitative review analysis of case-control studies reporting on PNN density in the postmortem brain of subjects with SCZ were performed. Results consisted of 7 studies that were included in the final analysis. The specific brain regions investigated in the studies varied, with most attention given to the dorsolateral prefrontal cortex (DLPFC; 3 studies) and amygdala (2 studies). Findings were mostly positive for reduced PNN density in SCZ, with 6 of the 7 studies reporting significant reductions and one reporting a tendency towards reduced PNN density. Overall, tissue processing methodologies were heterogeneous. Despite few studies, PNN density was consistently reduced in SCZ across different brain regions. These findings support evidence that implicates deficits in PNN density in the pathophysiology of SCZ. However, more studies, preferably using similar methodological approaches as well as replication of findings, are needed.